Pengaruh Pembuatan Mind Mapping di Akhir Pembelajaran dalam Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Siswa Kelas XI IPA SMA Kristen Gamaliel Makassar (Studi pada Materi Pokok Laju reaksi) - Rampean, Betzy Ayu Omega; Sulatry, Taty; Sudding, Sudding (Jurusan Kimia FMIPA UNM, 2021)
The research is a quasi-experimental that aimed to know the effect of making mind mapping at the end of learning in guided inkuiri learning model toward students’ learning outcome in XI IPA class of SMA Kristen Gamaliel Makassar. The independent variable in this experiment is making mind mapping at the end of lerning with use inquiri learning model. The dependent variable was the students’ learning outcome on the subject matter of reaction rate. The population was XI IPA with 4 classes of SMA Kristen Gamaliel Makassar and sample classes consisted of two classes, namely XI IPA1 class as an experiment class and XI IPA2 class as a control class with 33 students in each classes. Taking technique of sample was a simple random sampling. The research data was gathered by learning outcome test of reaction rate subject matter for post-test which was analyzed by using Mann-Whitney test. The result of hypothesis with Mann-Whitney test was Zcalculated = 1.70 at α = 0.05 obtained Ztable = 1.64. Therefore, Zcalculated > Ztable, which the H1 accepted and H0 rejected. It showed that there is an effect of making mind mapping at the end of learning in guided inkuiri learning model toward students’ learning outcome in XI IPA class of SMA Kristen Gamaliel Makassar on reaction subject matter.